2001
DOI: 10.1016/s1388-9842(00)00149-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and aetiology of heart failure in an Arab population

Abstract: Background: The epidemiology of heart failure in Arabia, with a population different from the West in cultural and ethnic origin, has not been studied before. Aims: To determine the prevalence and aetiologies of symptomatic heart failure in an indigenous Arab population over a 3-year period. Methods: All patients with heart failure G 13 years of age, treated at the only secondary care hospital of the Dhakliya region of Oman between 1992 and 1994 were evaluated prospectively by clinical history and physical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…In the most recent available national mortality data from Iran (2004), IHD The International Classification of Diseases (ICD10 codes I20 to I25) was the cause of 21.8% of all mortality cases in Iran, approximately 7-times more than hypertensive HD (ICD 10 codes I10 to I13, which included heat failure), which was the cause of death in 3.2% of cases. 38 Similarly, in the few available reports on incidence in Iran, HF was associated with IHD in 60-65% of admitted patients, 39 40 with similar proportions observed in studies from adjacent countries (40-60%), [41][42][43][44][45] and those from the West. 5 46 Furthermore, we analysed medication use in our study and observed that only 5% of our cases used digoxin, a medication commonly prescribed for symptomatic HF, 47 48 and even among those using digoxin, one-third also used nitrate compounds, indicated for IHD.…”
Section: Discussionmentioning
confidence: 74%
“…In the most recent available national mortality data from Iran (2004), IHD The International Classification of Diseases (ICD10 codes I20 to I25) was the cause of 21.8% of all mortality cases in Iran, approximately 7-times more than hypertensive HD (ICD 10 codes I10 to I13, which included heat failure), which was the cause of death in 3.2% of cases. 38 Similarly, in the few available reports on incidence in Iran, HF was associated with IHD in 60-65% of admitted patients, 39 40 with similar proportions observed in studies from adjacent countries (40-60%), [41][42][43][44][45] and those from the West. 5 46 Furthermore, we analysed medication use in our study and observed that only 5% of our cases used digoxin, a medication commonly prescribed for symptomatic HF, 47 48 and even among those using digoxin, one-third also used nitrate compounds, indicated for IHD.…”
Section: Discussionmentioning
confidence: 74%
“…South Asia was excluded from the analysis because the one paper screened from this region did not include data on participants’ age;[16] Middle East was excluded because only one study met inclusion criteria. [17] Therefore, results were estimated for six geographic regions. A paper from Singapore was excluded because 1) the relatively small size of the Singapore population compared with those of South Korea and Japan, 2) the participants’ ethnicities differed markedly from the other Asia Pacific High Income region studies (60% Chinese, 24% Malay, and 15% Indian ethnicities), and 3) a distinctly different heart failure risk factor pattern appeared (for example, 85% IHD).…”
Section: Methodsmentioning
confidence: 99%
“…In Western populations, between 6 and 10% of cases of heart failure are thought to be due to hypertension, 107,108 with significant ethnic variations. 109 Hypertension increases the risk of heart failure twofold in men and threefold in women over that seen in normotensive subjects. 110 Hypertension in men is more likely than in women to cause systolic heart failure.…”
Section: Hypertensionmentioning
confidence: 99%